Exploring The Marketing Performance of Pemalang Muslim Fashion SMEs Through Religious Product Advantage Strategy - Hanfan, Ahmad; Nupus, Hayati; Setiawan, Ahmad Ikhwan; D.S., Sitti Hartinah; Gunistiyo, Gunistiyo; Tabrani, Tabrani (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2024)
This study aims to determine the role of religious product advantage strategies to improve marketing performance in Pemalang Muslim fashion SMEs, Central Java. This is done by analyzing influence of entrepreneurial orientation on religious product advantage strategy, market orientation on religious product advantage strategy, religious product advantage strategy on marketing performance, entrepreneurial orientation on marketing performance and market orientation on marketing performance. This research was based on research gap on influence of entrepreneurial orientation on marketing performance and influence of market orientation on marketing performance. There are several research findings on entrepreneurial orientation and market orientation which influence marketing performance, but there are also several studies with the opposite results. This phenomenon raises the question of what should be done to improve marketing performance. A concept, religious product advantage strategy, is proposed in this study as a variable that plays an important role in improving marketing performance. This research developed five hypotheses and tested them using data collected from 108 respondents. Samples were obtained using purposive sampling techniques and statistical tests on a number of data processed with AMOS 22.0. The results found that religious product advantage strategy could increase marketing performance of Pemalang Muslim fashion SMEs.